2021
DOI: 10.3390/su13158235
|View full text |Cite
|
Sign up to set email alerts
|

Stated Preferences for Plant-Based and Cultured Meat: A Choice Experiment Study of Spanish Consumers

Abstract: Meat production and consumption have been claimed to have negative impacts on the environment, and even on the consumer’s health. In this sense, alternative sources of protein, mainly meat substitutes and cultured meat, have emerged due to those perceived negative effects. Our paper carries out a choice experiment to analyze the preferences of 444 Spanish consumers and their willingness to pay for plant-based and cultured meats, as compared to conventional meat. Spain was considered of interest for this study … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
13
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4
4
1

Relationship

1
8

Authors

Journals

citations
Cited by 26 publications
(14 citation statements)
references
References 82 publications
1
13
0
Order By: Relevance
“…Focusing on the meat alternatives, consumers have a significantly higher trust in plantbased foods compared to insect protein-based products and cultured meat. This trust ranking for alternative proteins is in line with the preference ranking found for these product types in literature [12,44]. From this, it can be concluded that trust in the analysed meat alternatives is a good predictor and antecedent for the final preference in the same products.…”
Section: Impact Of Meas Fns Organic Index and Social Trust On Trust I...supporting
confidence: 87%
“…Focusing on the meat alternatives, consumers have a significantly higher trust in plantbased foods compared to insect protein-based products and cultured meat. This trust ranking for alternative proteins is in line with the preference ranking found for these product types in literature [12,44]. From this, it can be concluded that trust in the analysed meat alternatives is a good predictor and antecedent for the final preference in the same products.…”
Section: Impact Of Meas Fns Organic Index and Social Trust On Trust I...supporting
confidence: 87%
“…Cheap talk was used to correct the hypothetical bias that can arise in this type of study. Thus, in line with previous research [ 13 ], a text explaining the hypothetical bias and its importance in the validity of the study was incorporated into the questionnaire, as shown in Table S1 in the electronic supplement. Finally, participants were asked to try to provide their unbiased answers to the CE, trying to actively put themselves in a real shopping situation.…”
Section: Methodsmentioning
confidence: 99%
“…This has driven the food industry to begin the development of new food products with additional benefits to consumer health [ 12 ]. Products such as “meat substitutes” (products made from alternative protein sources such as vegetables, algae, insects, and mycobacteria) and “cultured meat”, which attempt to offer alternatives to a number of consumer preferences [ 13 ], have recently entered the market. However, not all the consumers from western countries are willing to reduce their meat consumption [ 14 , 15 , 16 , 17 ].…”
Section: Introductionmentioning
confidence: 99%
“…A five-point Likert scale was used to investigate the level of agreement for each statement (1: strongly disagree; 2: disagree; 3: neutral; 4: agree; 5: strongly agree). Consumer preferences were elicited using a hypothetical discrete choice experiment approach (DCE), which is widely applied due to its ability to simulate real market situations and improve participant response rate [30].…”
Section: Methodological Procedures and Data Collectionmentioning
confidence: 99%